An Analysıs Into Demographıc Effect On Stress Level Among Employees In Prıvate Colleges - Ramamoorthy R , Dr Ravikumar A (International Journal of Advanced Science and Technology, 2020)
Stress impacts everyone in the workplace. Irrespective of the kind of work a person does his economic back ground or his age no one is immune from stress. It have effect on family well-being and health of an individual. The WHO says that stress is an “Epidemic across Globe”. The United Nation Organization calls the stress resulting from job as “the disease of 20th Century” The frightening reality is that “Immunity is completely absent against stress”, for it can affect anyone. Stress in the workplace, is due to the inter-connected, competitive and profit-driven organizational culture, these features along with “round-the-clock” connectivity through cell phones and computers also add to stress levels. From the analysis it is found that there is no significant difference between considered demographic factors and parameters.